Integrated compensation model using a three-phase neutral point clamped inverter - Chau Minh Thuyen; Nguyen Hoai Thuong; Truong Khac Tung (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Normally, when research on active compensation models, previous studies only assumed that the source of harmonics is nonlinear load. The nonlinear load here is fixed and balanced, the supply voltage is considered ideal, i.e. the three-phase source is balanced and there is no distortion. However, in reality, the above assumption is difficult to achieve. Therefore, this paper aims to design an integrated compensation model for different types of harmonic sources. The types of harmonic sources considered here include: harmonic sources generated from nonlinear load and source. The requirement of the integrated compensation model is to create a balanced three-phase voltage at the terminal of the load and the supply current must be a sinusoidal wave in phase with the source voltage. In order to reduce the loss caused by the inverter switching, this paper uses a three-level Neutral Point Clamped inverter. The simulation results performed on Psim software have demonstrated the effectiveness of the proposed integrated compensation model compared to the traditional integrated compensation model in reducing harmonics and stabilizing DC-bus voltage.